Self-perceived health status among young adults: Does a differentiated minimum wage cut matter? - Alexandros P. Bechlioulis; Michael Chletsos; Alexandra V. Gkliati; Anna Saiti (SPOUDAI - Journal of Economics and Business, 2022)
The paper investigates whether the imposition of a higher minimum wage cut on very young adults (17-24) differentiates their self-perceived health status compared to that of young adults (25-29). We use data from the Hellenic Statistical Authority over the period between 2010 and 2014 in Greece. Our results are clear: a higher decrease of the minimum wage for very young adults is associated with a higher possibility of an increasing fair reported health status. This possibility is significant only when potential workers are considered; however, this possibility is not an issue neither among young employees nor for inactive young adults.
Keywords: I10; I18; J08; 330; difference-in-differences estimation technique; minimum wage reform; self-perceived health status; young workers